Analysis of the Competence of Islamic Religious Education Teachers in Implementing Differentiated Learning at SMP Ibnu Sina Pesantren-Based School in Pagar Alam City - Hasanah, Mauizatun; Alfarabi, Thoriq (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Differentiated learning is an approach that accommodates the diverse characteristics and learning needs of students. This study aims to analyze the competence of teachers in implementing differentiated learning in the Islamic Religious Education (PAI) subject at SMP Ibnu Sina Pagaralam, which is based on a pesantren model. The research focuses on the teacher's understanding of the concept of differentiated learning, the implementation of learning strategies, and the challenges faced in its application. This study uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and document studies. The subjects of the research are the PAI teachers at SMP Ibnu Sina Pagaralam. The data were analyzed using descriptive qualitative analysis with stages of data reduction, data presentation, and conclusion drawing. The results show that PAI teachers at SMP Ibnu Sina have a sufficient conceptual understanding but have not yet fully implemented it consistently and comprehensively in the learning process. This is due to a combination of internal and external factors that directly affect the teacher's competence. Supporting factors, such as regular training, flexible teaching materials, and the support of the school principal, strengthen the teacher's capacity to apply the differentiated approach. This study concludes that the competence of teachers in implementing differentiated learning needs to be further improved through continuous training and adequate infrastructure support.